2008
DOI: 10.1002/ejic.200800946
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Porphyrinoids from a Biomimetically Decorated Bipyrrole

Abstract: The known 5,5′‐diformyl‐3,3′‐bis(methoxycarbonylethyl)‐4,4′‐dimethyl‐2,2′‐bipyrrole was employed in the preparation of biomimetic functional porphyrinoids. Tetrapyrrolic 2,2′‐bidipyrrins could be obtained from condensations with two equivalents of 3,4‐dialkyl‐2‐methylpyrroles. From these compounds, a manganese(III) corrole as well as a boron‐containing bis(bodipy) fluorophor are accessible as functional species in one‐step reactions. Both products were investigated by means of X‐ray crystallography. Attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 96 publications
(17 reference statements)
2
15
0
Order By: Relevance
“…Figure reveals a small but distinct bond-length alternation in and around the bipyrrole unit of the three MnCl structures. An analogous bond-length alternation is also found for other structurally characterized halogenomanganese corroles (MIKWOU, TORMET, YAWQES, YAWQAO, GIFJEL, and XIDRUY) but is essentially nonexistent in the X-ray structure of Mn­[T p OMePC]­Ph (as well as CISGUH and CISHAO). We have recently shown that such a bond-length alternation is indicative of a corrole a 2u -type radical (allowing ourselves to use D 4 h symbols for orbital symmetries that are standard for porphyrins). DFT calculations also reproduce this difference in the skeletal bond-length alternation between Mn­[TPC]Cl and Mn­[TPC]­Ph (Figure ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Figure reveals a small but distinct bond-length alternation in and around the bipyrrole unit of the three MnCl structures. An analogous bond-length alternation is also found for other structurally characterized halogenomanganese corroles (MIKWOU, TORMET, YAWQES, YAWQAO, GIFJEL, and XIDRUY) but is essentially nonexistent in the X-ray structure of Mn­[T p OMePC]­Ph (as well as CISGUH and CISHAO). We have recently shown that such a bond-length alternation is indicative of a corrole a 2u -type radical (allowing ourselves to use D 4 h symbols for orbital symmetries that are standard for porphyrins). DFT calculations also reproduce this difference in the skeletal bond-length alternation between Mn­[TPC]Cl and Mn­[TPC]­Ph (Figure ).…”
Section: Resultssupporting
confidence: 69%
“…Thus, Table 3 shows that halogenomanganese corroles (including the previously reported structures MIKWOU, 41 TORMET, 44 YAWQES, 14 YAWQAO, 14 GIFJEL, 45 and XI-DRUY 42 ) exhibit significantly larger out-of-plane Mn−N 4 displacements than Mn-aryl corroles (including CISGUH 35 and CISHAO 35 ). The higher displacements for the MnCl complexes facilitate antiferromagnetic coupling between the d z 2 electron of the high-spin Mn III center and the "a 2u -type" corrole radical.…”
Section: ■ Introductionmentioning
confidence: 75%
“…[4,5] Nevertheless, all efforts to obtain a suitable single crystal of complex 1 were unsuccessful, which hindered a detailed structural view of this complex. Thus, comparison was carried out on similar complexes with known solid-state structures.…”
Section: Introductionmentioning
confidence: 99%
“…And 19 F NMR gives no signal of any resonance, further proving the absence of BF 2 group. Although BODIPY dyes normally exhibit high chemical-and photo-stability, decomposition also happens in certain chemical conditions, especially under attack of radicals in this case [33,34]. Ligand L2 could also be synthesized through bromination of L1 by bromine with excellent yield (82%), following previously reported procedure [35].…”
mentioning
confidence: 98%